Genotypes of Rhizophora Propagules From a Non-mangrove Beach Provide Evidence of Recent Long-Distance Dispersal - Ngeve, Magdalene N.; Koedam, Nico; Triest, Ludwig (Frontiers in Conservation Science, 2021)
Dispersal plays a crucial role in the connectivity of established mangrove populations and in species range dynamics. As species ranges shift in response to climate change, range expansions can occur from incremental short-distance dispersal events and from stochastic long-distance dispersal events. Most population genetic research dealt with historically accumulated events though evidence of actual propagule dispersal allows to estimate genotypic features and origin of founders. In this study we aim to disentangle a contemporary dispersal event. Using microsatellite markers, we genotyped 60 Rhizophora racemosa drift propagules obtained on a bare unforested coastal area in southern Cameroon, estimated their relationship to 109 adult trees from most proximate sites (which were 3 to 85 km away), and assessed their relative difference with 873 trees of major mangrove areas (> 300 km) along the Cameroonian coastline. Proximate mangrove populations were considered as potential source populations in assignment tests. However, drift propagules could not be assigned to any of the Cameroonian mangrove sites and were genetically isolated from Cameroonian populations. Drift propagules showed higher levels of genetic diversity and private alleles giving a higher relatedness to each other than to any putative source population. Chloroplast sequences were used to confirm the identity of drift propagules as R. racemosa. We postulate that a complex interaction of ocean currents, estuarine geomorphology, and tidal patterns explain drift propagule dispersal to an area. Most likely the investigated cohort of propagules originated from more southern mangrove areas of the West African range beyond the Cameroonian border. This study unraveled the allelic, genetic, and genotypic features of stranded propagules following a stochastic long-distance dispersal. Transboundary dispersal of these propagules highlights the need for intergovernmental efforts in the management of biodiversity.